Deakin, Michael A.B., “Boole’s Mathematical Blindness”, Math. Gaz. 80 (1996), 511–518 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Russell, Bertrand, "Introduction to Mathematical Philosophy. With a New Introduction by John G. Slater", Reprint der Ausgabe von 1919, Routledge: London/New York 1993 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Sandu, Gabriel, “IF First-Order Logic, Kripke, and 3-Valued Logic”, in: J. Hintikka, The Principles of Mathematics Revisited, Cambridge 1996, 254–270 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Lorenz, Stefan, "De mundo optimo: Studien zu Leibniz’ Theodizee und ihrer Rezeption in Deutschland (1710–1791)", Franz Steiner Verlag: Stuttgart 1997 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Hovens, Frans, “Lotze and Frege: The Dating of the ‘Kernsätze’”, In: History and Philosophy of Logic 18 (1997), 17–31 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Whitehead, Alfred North/Russell, Bertrand, "Principia Mathematica to *56", Cambridge University Press: Cambridge 1997 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

McGinn, Marie, "Wittgenstein and the Philosophical Investigations", Routledge: London 1997 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Beller, Walter, “Logic in Mexico”, In: Santiago Ramirez (ed.), Mexican Studies in the History and Philosophy of Science, Kluwer: Dordrecht 1995 (= Boston Stud. Philos. Sci.; 172), 1–22 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Schulz, Klaus-Dieter, "Die These von Church. Zur erkenntnistheoretischen und sprachphilosophischen Bedeutung der Rekursionstheorie", Peter Lang: Frankfurt a.M. u.a. 1997 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Buschlinger, Wolfgang, "Wider das Verbot der semantischen Geschlossenheit der Sprache. Der Wert unliebsamer sprachlicher Strukturen für die Reduktion von Graphentheorie auf Logik", Peter Lang: Frankfurt a.M. 1997 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Christidis, Theodor, “Philosophical and Mathematical Premises to the Development of Mechanics of Lagrange” In: Nonlinear Analysis, Theory, Methods & Applications 30, No. 4 (1997), 2107–2112 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Landini, Gregory, “Logic in Russell’s Principles of Mathematics”, In: Notre Dame Journal of Formal Logic 37, Nr. 4 (1996), 554–584 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Janich, Peter, "Euclid’s Heritage: Is Space Three-dimensional?", Dordrecht: Kluwer Academic Publishers 1992 (= The University of Western Ontario Series in Philosophy; 52) - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Rodych, Victor, “Wittgenstein on Mathematical Meaningfulness, Decidability, and Application” In: Notre Dame Journal of Formal Logic 38 (1997), Nr. 2, 195–224 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete [)

Cobos, J., “A Mathematician out of his Time: Ventura Reyes Prosper”, In: Extr. Math. 11, Nr. 2 (1996), 306–314 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Berning, Matthias, " Analysis und Determination. Eine Studie zur Erkenntnistheorie der Mathematik bei Descartes", Hartung-Gorre Verlag: Konstanz 1997 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Ihmig, Karl-Norbert, „Hilberts axiomatische Methode und der Fortschritt in den Naturwissenschaften. Zu Cassirers Wissenschaftsphilosophie“, in: Rudolph, Enno/Stamatescu, Ion O. (eds.), Von der Philosophie zur Wissenschaft: Cassirers Dialog mit der Naturwissenschaft, Meiner: Hamburg 1997, 63–91 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Gabriel, Gottfried/Kienzler, Wolfgang (eds.), "Frege in Jena. Beiträge zur Spurensicherung. Tagungsbericht, Jena, Deutschland, 6.–7. Dezember 1996", Königshausen & Neumann: Würzburg 1997 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Erkenntnistheorie als Wissenschaft: Streitpunkte zwischen Husserl, Gurwitsch, Merleau-Ponty und Piaget - Scharlau, Ingrid

Experiments with the role-playing method in the study of interactive behavior - Hofer, Manfred; Buhl, Heike M. (Verbal interaction and development in families with adolescents)

Spektakel des Geschlechts. Schaulust und Körperpolitik in Elfriede Jelineks Die Klavierspielerin - Öhlschläger, Claudia; Barz, Sabine (kea. Zeitschrift für Kulturwissenschaften: KörperBilder-KörperPolitiken)

Garant des Wunsches. Zur Opferung des Sündenbocks in Oscar Wildes Salome - Öhlschläger, Claudia (Figuren der/des Dritten. Erkundungen kultureller Zwischenräume)

Das Leiden an den und für die Österreicher. Thomas Bernhards „Heldenplatz“ - Steigerwald, Jörn (Nationale Identität. Aspekte, Probleme und Kontroversen in der deutschsprachigen Literatur)

Lemma McLuhan, Herbert Marshall - Steigerwald, Jörn (Metzler Lexikon Literatur- und Kulturtheorie. Stuttgart/Weimar 1998, S. 347-348; Stuttgart/Weimar 20012, S. 409-410; Stuttgart/Weimar 2004, S. 426-427)

Deuterium NMR Investigations of Liquid Crystals During Shear Flow - Schmidt, Claudia; Müller, Stefan; Siebert, Hartmut (Dynamics of Complex Fluids)

Shear Orientation of Lyotropic Hexagonal Phases - Schmidt, Gudrun; Müller, Stefan; Lindner, Peter; Schmidt, Claudia; Richtering, Walter (The Journal of Physical Chemistry B)
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Physical and Theoretical Chemistry

Behavior under flow of side chain liquid crystal polymers - Quijada Garrido, Isabel; Siebert, Hartmut; Schmidt, Claudia; Friedrich, Christian (Progress and Trends in Rheology V (5th European Rheology Conference))

Magnetic Resonance - Schmidt, Claudia; Spiess, Hans Wolfgang (Handbook of Liquid Crystals Set)

In situ NMR studies of liquid crystals in shear flow - Schmidt, Claudia; Becker, Patrick; Hasenhindl, Alfred; Müller, Stefan; Siebert, Hartmut (Progress and Trends in Rheology V (5th European Rheology Conference))

Rheology and NMR measurements of sodium dodecyl sulphate/decanol/water nematics - Thiele, T.; Berret, J. F.; Muller, S.; Schmidt, Claudia

Tommaso Campanella: Philosophische Gedichte. Übersetzt und hrsg. von Thomas Flasch. Frankfurt a. M.: Klostermann, 1996 - Hagengruber, Ruth Edith (Philosophischer Literaturanzeiger)

Widersprüche, Paradoxien und Klärungen. Überlegungen grundsätzlicher Art zur Frauenforschung aus der Sicht von Philosophinnen - Hagengruber, Ruth Edith (Perspektiven der Frauenforschung)

Philosophinnen - Hagengruber, Ruth Edith (Feministische Hochschuldidaktik. Materialien der Koblenzer Frauenstudien)

Utility and Universality versus Utility and the General Good - Hagengruber, Ruth Edith (presented at the XXth World Congress of Philosophy Boston)

Wirtschaften als Erhalt der Güter – eine Utopie? - Hagengruber, Ruth Edith (Ethica. Wissenschaft und Verantwortung)

Commynes und der Umgang mit der Öffentlichkeit im 15. Jahrhundert - Kamp, Hermann (Das Öffentliche und Private in der Vormoderne)

Moderne Herrschaftsformen vor der Moderne: das Beispiel Burgund - Kamp, Hermann (Menschen im Schatten der Kathedrale. Neuigkeiten aus dem Mittelalter)

Berufsorientierung in Zeiten der Krise: Thematisierung - Dethematisierung. - Bigga, Regine (Schule und Arbeitswelt. Zwischen Thematisierung und De-Thematisierung von Geschlecht.)

Anregungen für die Lehrplanarbeit hinsichtlich der Gleichstellung der Geschlechter. Lehrpläne für Mädchen und Jungen. - Bigga, Regine (Lisa-Jahrbuch)

Angepaßte Monologe? Über die Konsequenzen ‚radikaler‘ De-Ontologisierung und konventioneller Performanz - Weber, Jutta (Ethik und Sozialwissenschaften. Dezember 1998)

Feminismus & Konstruktivismus. Zur Netzwerktheorie bei Donna Haraway - Weber, Jutta (Das Argument. Zeitschrift für Philosophie und Sozialwissenschaften Vol. 227, Nr. 5)

Die Sinfonie im deutschen Kulturgebiet 1850 bis 1875. Ein Beitrag zur Gattungs- und Institutionengeschichte - Grotjahn, Rebecca

VIPspace - A Visually Programmable Shared Workspace - Dücker, M.; Müller, Wolfgang; Rubart, Jessica (Proceedings. 1998 IEEE Symposium on Visual Languages)
With the wide availability of network supporting hard-and software cooperative computer-based environments became extremely popular. A wide range of CSCW (Computer Supported Cooperative Work) tools with video conferencing, electronic mail, shared whiteboards, discussion forums, and shared information systems are already part of daily business. In contrast to the unstructured linear stream of information in electronic mails shared workspaces provide structured administration of electronic information like documents, voice, pictures, and movies. Popular examples of shared workspaces are BSCW (Basic Support for Cooperative Work), Hypernews, Lotus Notes, Alta Vista Forum, Lifelink, Microsoft Exchange and Webshare. Currently, all these systems are not flexible enough to get easily customized to the requirements of the individual application and user only supporting a limited set of predefined different views and functionality. This article introduces VIPspace (Visually Programmable Workspace). VIPspace can be easily customized to the individual needs of an user through VIPrule, a combination of a form- and icon-based visual programming language. VIPrule is based on an easy-to-use drag and drop paradigm. Direct manipulation via drag and drop allows easy access to local file systems as well as manipulation, exchange, and publication of shared multimedia documents. As VIPspace is implemented in Java it nicely integrates with other web-applications and provides a platform independent environment with a uniform graphical user interface.
Keywords: Collaborative work; Electronic mail; Computer networks; Video sharing; Videoconference; Discussion forums; Information systems; Streaming media; Motion pictures; Computer languages

Authoring Communicating Agents in Virtual Environments - Geiger, Christian; Lehrenfeld, Georg; Müller, Wolfgang (Proceedings of the Annual Conference for the Computer Human Interaction)
3D-graphics popularity has steadily increased in a number of areas such as entertainment, scienti c vi- sualization, simulation, and virtual reality. Despite this rapid growth the authoring of animated 3D objects in virtual environments is stil l by no means trivial. This article presents new concepts of the animated 3D programming language SAM (Solid Agents in Motion) and its programming environment. In SAM, the main syntactic objects like agents, rules, and messages are represented as 3D objects. The design of a SAM pro- gram is supported by a dedicated 3D structure editor. The editor al lows the de nition and spatial arrange- ment of SAM agents in a 3D scene by direct manipu- lation. The paper gives a number of SAM examples, demonstrating the authoring of simple animated vir- tual 3D scenarios.

Die schwarze Braut der Romantik. (De)Konstruktionen von Muttermythen bei Clemens Brentano und Dorothea Schlegel - Morrien, Rita (Freiburger FrauenStudien – Zeitschrift für Interdisziplinäre Frauenforschung)

10-Gb/s PMD compensation using deformed-helical ferroelectric liquid crystals - Sandel, D; Hinz, S; Yoshida-Dierolf, M; Graser, J; Noé, Reinhold; Beresnev, L; Weyrauch, T; Haase, W (24TH EUROPEAN CONFERENCE ON OPTICAL COMMUNICATION, VOL 1-3: VOL 1: REGULAR AND INVITED PAPERS; VOL 2: TUTORIALS AND SYMPOSIUM PAPERS; VOL 3: POSTDEADLINE PAPERS)

Polarisation mode dispersion compensation at 20Gbit/s with fibre-based distributed equaliser - Noé, Reinhold; Sandel, D; Yoshida-Dierolf, M; Hinz, S; Glingener, C; Scheerer, C; Schopflin, A; Fischer, G (ELECTRONICS LETTERS)

Influence of polarization on 30 GHz broadband radio channels - Karthaus, U; Noé, Reinhold (1998 INTERNATIONAL ZURICH SEMINAR ON BROADBAND COMMUNICATIONS: ACCESSING, TRANSMISSION, NETWORKING)

Automatic polarisation mode dispersion compensation in 40Gbit/s optical transmission system - Sandel, D; Yoshida-Dierolf, M; Noé, Reinhold; Schopflin, A; Gottwald, E; Fischer, G (ELECTRONICS LETTERS)

Optical network analysis and longitudinal structure characterization of fiber Bragg grating - Sandel, D; Noé, Reinhold; Heise, G; Borchert, B (JOURNAL OF LIGHTWAVE TECHNOLOGY)